Analysis of a drilling mud-based system on the common problems related to coiled tubing application in slim-hole oil wells - Rahman, Muhammad Rafli Abdual; Busahmin, Bashir; Hasan, Ummul Hasanah Hj (Edelweiss Applied Science and Technology, 2023)
Coil tubing is slim and looks like a long, continuous length of pipe made from carbon steel metal that is a lesion on spool that is 1 to 3.25 inches in diameter of 26,000 feet long. The main benefit of coil tubing in drilling operations over wireline jobs is the ability to pump chemicals through the coil and the ability to push it into the hole rather than relying on gravity. Inappropriate selection of the drilling mud is one of the contributing factors to hole problems. Different experiments were conducted to determine the mud rheology of multiple mud samples. Certain parameters, like the critical velocity, are calculated using a numerical approach for the coiled tubing applications. In addition, it is crucial to determine the pump pressure required to maintain a specific flow rate. It is noted that drilling operations become more efficient at lower plastic viscosities; however, plastic viscosity is reduced through dilution; hence, the rate of penetration is improved. Moreover, a higher yield point is capable of transporting the cuttings more effectively than a lower yield point. The critical velocity indicated the boundaries between the laminar and turbulent flow regimes. As the mud flow rate inside the tubing increased, the velocity increased, causing the shear stress at the tubing wall to increase.